Determinants of the Levels of Development Based on the Human Development Index:Bayesian Ordered Probit Model - Çağlayan-Akay, Ebru; Van, Muhammed H. (International Journal of Economics and Financial Issues, 2017)
The aim of the paper is to determine the factors affecting the economic development levels of selected countries using bayesian ordered probit model. For this aim, Human Development Indices of 130 countries are involved in the analysis with respect to seven independent variables for the period of 2009-2014. According to the results obtained from the Bayesian ordered probit model, it was observed that while the variables of rural population, health expenditure, GDP, internet users, life expectancy at birth, share of expected years of schooling seats in parliament had a positive effect on human development level in short term; the variables of health expenditure, GDP, internet users, share of expected years of schooling and seats in parliament had a positive effect, but rural population and life expectancy at birth had a negative impact on human development in long term. Keywords: Human Development Indices, Ordered probit, Bayesyen, Economic development JEL Classifications: O150, C250, C110, O100